To determine the prevalence and improve the effectiveness treatment of dental diseases in patients with COVID-19. (Eurasian Medical Research Periodical, 2023)
The article presents the results of a study of the state of local immunity in the oral cavity in 30 patients with COVID-19, depending on the severity